Analysis of The Addition Polypropylene Fibre and 8670 Mn Viscocrete added Material on The Split Tensile Strength and Modulus of Elasticity of Concrete - Fahrizal Zulkarnain; Rizki Efrida; Sri Frapanti (Jurnal Penelitian Pendidikan IPA, 2023)
This study used waste coconut fibre and HDPE plastic as partial aggregate replacement materials. Coconut fibre ash has pozzolanic properties, which contain high silicate elements. High-density polyethene (HDPE) plastic has more potent, complex, opaque material properties and is more resistant to high temperatures. Superplasticizer is an admixture added to concrete during mixing and during placing to improve its strength performance. This study aims to study the effect of adding HDPE plastic as a substitute for coarse aggregate, coconut fibre ash as a substitute for fine aggregate and Viscrocrete-8670 MN on absorption, concrete compressive strength and elastic modulus of concrete. With variations in the addition of BN HDPE plastic, 0.5%, 1%, and 1.5%, the coarse aggregate passed 3/8 filter retained by filter no 4, 3% coconut fibre ash for each variation of concrete and Viscrocrete-8670 MN by 0.8% by weight of cement. The maximum value for each concrete test is the absorption value of concrete (4.23% for regular concrete), compressive strength (32.49 MPa for 1.5% HDPE concrete), and the modulus of elasticity (3152 MPa for 1.5% HDPE concrete).